(untitled) (Pedagogy of Higher and Secondary Education, 2013)
Polyakova V. Y. Didactic adaptation of forms, methods, techniques, methods of independent cognitive activity in the paradigm of high school student – a student of higher academic institutions. Didactic adaptation of forms, methods, techniques, methods of independent cognitive activity in the paradigm of high school student - a student of higher academic institutions as one of the conditions for the organization of teaching self-learning activities of students of high school is considered on the basis of psycho-pedagogical analysis.